Tájhasználat és gazdasági térszervezés a középkori Magyarországon - Frisnyák, Sándor (Közép-Európai Közlemények, 2013)
The paper summarizes land use and economic spatial structure in Hungary (= Carpathian Basin) during the Middle Ages. The process analysis begins from the Hungarian conquest of the Carpathian Basin (895-900) and lasts until the turn of the 15th and 16th century. Hungarians settled down in the lowlands and other hilly areas located in the centre of the Carpathian Basin (220.000 km2). The occupation and economic take-over of the mountain ranges surrounding the basin took place by the end of the 13th century, and people immigrating from the west and east played an important role in this process. The reshaping of the natural ecosystem, the creation, operation and development of economic space (cultural landscapes) is the common result of the work of Hungarians living together with other ethnic groups. Land use in Hungary during the Middle Ages can be summarized as follows: (1) monoculture animal husbandry in floodplains (50–60 km wide), (2) monoculture cereal cropping in areas prevented from floods (‘larders’), (3) polyculture in hilly areas with significant grape-and wine-growing in some regions, (4) industrial activity in mountainous areas (gold and silver mining with European significance), forestry, alpine pastoralism, farming in valleys and inter-mountain basins.